GROWTH IN VITRO OF Schomburgkia crispa Lindley IN THE INCREASED CULTURE OF Salvia hispanica L - Assis, K. C.C. [UNESP]; Guardabaxo, C. M.S.; Begueline, M. C.L.M. [UNESP]; Rezende, B. N. [UNESP]; Silva, L. F. [UNESP]; Maciel, A. L.R. (Universidade Estadual Paulista - Campus de Tupa, 2020)
The use of alternative culture media for the in vitro cultivation of plants is being increasingly used to meet nutritional needs, reducing production costs. In this context, the present work aimed to evaluate the influence of the concentrations of salts of the MS culture medium and of the chia extract on the in vitro growth of seedlings of Shamburquia crispa Lindley. The experimental design used was completely randomized-DIC, in a 5x5 factorial scheme, with the treatments being composed of different concentrations of salts of the MS culture medium (0, 25, 50, 75 and 100%) and concentrations of chia extract (0, 3.5, 7.0, 10.5 and 14.0 g L-1), with four replications and four seedlings per plot. The data were submitted to analysis of variance and, to compare the treatment means, the Scott Knott test was performed at 5% significance. All analyzes were performed with the aid of the SISVAR 5.3 program. After 90 days of installation, the following were analyzed: survival rate (%), number of leaves, number of roots, length of the largest root and length of the aerial part. The reduction in salts of the MS culture medium (0, 25 and 50%) associated with the addition of chia extract (10.5 and 14 g L-1) promotes greater growth and development of Schomburgkia crispa Lindley explants grown in vitro.
CRESCIMENTO IN VITRO DE Schomburgkia crispa Lindley EM MEIO DE CULTURA ACRESCIDO DE Salvia hispanica L
Keywords: Culture medium; Explants; Orchids